PRAGMATIC ANALYSIS OF DEIXIS IN THE NOVEL FANGIRL BY RAINBOW ROWELL - Ervina CM Simatupang; Najmah Nur Fadhilah; Rezky Afiahtul Barokah (English Journal Literacy Utama, 2021)
The purposes of this study are to analyze the types of deixis, the functions of deixis, and the factors of deixis in the novel Fangirl. The writer used qualitative descriptive method with the theory from Nazir (2013). In analyzing the data, the writer used the theories about pragmatics from Mey (1993), Leech (1983), and Yule (1996). The writer also used the theories about deixis from Cruse (2000), Levinson (1983), and Kreidler (1998). The results show (1) there are 30 data of five deixis types found in the novel Fangirl consisting: 6 data (20%) of person deixis, 4 data (13,3%) of place deixis, 7 data (23,3%) of time deixis, 7 data (23,3%) of discourse deixis, and 6 data (20%) of social deixis. (2) Deixis have different functions according to each types of deixis. They are to explain the participant role in speech acts (person deixis), to explain the relative location to the location of speaker and addressee (spatial deixis), to show the time when the speech occurs (time deixis), to show references contained in discourse of the speech acts (discourse deixis), and to show aspects of social relationship between the speaker and the addressee (social deixis). (3) The deixis factors found in the data analysis consisted of 5 factors: participant role (28.3%), usage function (51.7%), social status (3.3%), formality/informality (3.3%), and intimacy (13,3%).